MICROALGAE POTENTIAL TO DECREASING DISSOLVED AMONIA CONCENTRATION (NH3) ON LIQUID WASTE OF UREA FERTILIZER FACTORY - Fadjar Sidiq Hidayahtullah (Jurnal Ecolab, 2019)
The purpose of this research to analyzing the abilities of microalgae from various water treatment processes to improving chemical properties (pH, dissolved NH3, BOD, NO3-) the liquid waste of urea fertilizer factory. The sampling method has used the grab sampling method for a certain period. Microalgae sources are obtained from various water treatment processes and mixed with waste of water at a dose of 300 mg L-1. The results showed the source of microalgae clarifier was significantly different in reducing dissolved ammonia concentration, pH, and nitrate. Based on the results of regression analysis and correlation showed that the microalgae population was partially correlated with pH, BOD, nitrate, and dissolved ammonia of 1.61%, 87.70%, 55.38%, and 9.63%. While the concentration of dissolved ammonia significantly affected pH, BOD, nitrate, and microalgae biomass growth of 84.40%.